Sistem Pendaftaran Tanah di Indonesia Menurut Peraturan Pemerintah No. 24 Tahun 1997 Tentang Pendaftaran Tanah - Joko Widodo; Abdul Halim; Siti Muqhimatul Lulu’ah (AL-BURHAN, 2022)
Land registration contained in Article 1 point 1 of Government Regulation Number 24 of 1997 is a series of activities carried out by the Government continuously, continuously and regularly, including collection, processing, bookkeeping, and presentation and maintenance of physical data and juridical data, in the form of maps. and a list of land parcels and apartment units. This study aims to determine how the system of implementing land registration in Indonesia according to PP No. 24 of 1997 concerning land registration. The research method used is normative juridical research with primary and secondary data sources. In data collection techniques, namely data collection can be done in various settings, various sources and various ways, namely by collecting data from primary data sources and secondary data sources for analysis. and conclusions. The results of the research are that land registration aims to guarantee legal certainty and certainty of rights to the land. The LoGA emphasizes that land registration must be carried out in order to guarantee legal certainty in the land sector and the publication system is a negative system, but contains positive elements.